Reproductive performance and herd life of crossbred dairy cattle with different levels of European inheritance in Ethiopia - Negussie, E.; Brannang, E.; Rottmann, O.J. (Ethiopian Society of Animal Production, 2000)
The effect of levels of upgrading of indigenous Ethiopian cows on the reproductive performance and herd life of crossbreds with different levels (50, 75, and 87.5%) of European inheritance were evaluated. Genetic and non genetic factors affecting herd life and reproductive performance traits such as age at first calving (AFC), number of services per conception (NSC), days open (DO), gestation length (GL), and calving interval (CI) were also assessed. The results obtained showed that there is a significant difference in the reproductive performance among the different groups of crossbreds. Overall, F1 crosses were better than the rest of the crossbred groups. Among the first crosses, Jersey crosses were found to be the best. In general, upgrading indigenous breeds to higher levels (>50% Bos taurus inheritance) resulted in late AFC, more number of services required per conception, longer calving intervals and early removal of cows from the herd completing small number of lactation. Therefore, under tropical conditions, where the seasonal nature of feed availability and incidence of diseases limit high production, upgrading indigenous breeds to 50% European inheritance would be promising (especially with Jersey sires). Upgrading to 75% would also be suggested provided the level of management is good enough to meet the relatively higher environmental demand of these animals.